2021
DOI: 10.1111/1754-9485.13263
|View full text |Cite
|
Sign up to set email alerts
|

Proximal splenic embolisation versus distal splenic embolisation for management of focal distal arterial injuries of the spleen

Abstract: Introduction: To compare the outcomes of proximal (pSAE) versus distal (dSAE) splenic artery embolisation for management of focal distal arterial splenic injuries secondary to blunt splenic trauma. Method: Ethical approval was granted by the hospital research and ethics committee, Project 389/19. All patients who underwent splenic artery embolisation secondary to blunt abdominal trauma from 1 January 2009 to 1 January 2019 were reviewed. Patients with a tandem embolisation (both proximal and distal embolisatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Proximal embolization reduces perfusion pressure to the injury, allowing for physiologic hemostasis. However, some studies have reported a higher complication rate with proximal embolization, including rebleeding and need for splenectomy 21,23,24 …”
Section: Algorithmmentioning
confidence: 99%
See 2 more Smart Citations
“…Proximal embolization reduces perfusion pressure to the injury, allowing for physiologic hemostasis. However, some studies have reported a higher complication rate with proximal embolization, including rebleeding and need for splenectomy 21,23,24 …”
Section: Algorithmmentioning
confidence: 99%
“…However, some studies have reported a higher complication rate with proximal embolization, including rebleeding and need for splenectomy. 21,23,24 Agents used in splenic artery embolization include Gelfoam® (Pfizer Inc., Manhattan, New York) and coils.…”
Section: Embolization Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there was a statistically significant difference in fluoroscopy time between the proximal (10.1 ± 4.2 min) and distal groups (17.8 ± 8.7 min). Other studies [ 96 , 97 ] showed equivalent results between the two techniques regarding technical and clinical success. Proximal SAE was associated with fewer and smaller infarcts than distal SAE in a series of CT scans of the embolized spleen in another study [ 98 ].…”
Section: Methodsmentioning
confidence: 87%